Isomorphism, institutionalization and legitimacy: operational auditing at the court of auditors - Freitas, Carlos Alberto Sampaio de (2007)
The aim of this paper is to verify the nature of the relationship between the concept of legitimacy and the phenomenon of institutionalization of operational auditing at the Court of Auditors in a context of institutional isomorphism. A documental examination was conducted covering the period of 1987 to 2004 and 18 people involved in the aforementioned activity at the Court of Auditors were interviewed. The results suggest that there is a relationship between isomorphism and legitimacy but only concerning one type of legitimacy. The phenomenon of isomorphism acts in the sense of checking cognitive legitimacy while other factors are at work which are connected to the culture and institutional environment of the country, which interfere in the dimension of moral legitimacy, resulting in institutionalization of the activity at a secondary level in the analyzed organization. It was seen that the process of institutionalization, in this case, has a circular characteristic, in which the phases of innovation, diffusion, partial saturation and partial deinstitutionalization follow one another cyclically, modifying the activity of operational auditing over time at the Court of Auditors.